Amphiphilic silane modified multifunctional nanoparticles for ratiometric oxygen sensing. Issue 54 (7th July 2017) - Lin, Yanxia; Xu, Hongwei; Dong, Biao; Sun, Xueke; Li, Chunhe; Li, Jianing; Xu, Lin; Bai, Xue; Song, Hongwei
Abstract : Precise detection of dissolved oxygen (DO) at the cellular level plays a pivotal role in the diagnosis of many diseases and intraoperative observation. Abstract : Precise detection of dissolved oxygen (DO) at the cellular level plays a pivotal role in the diagnosis of many diseases and intraoperative observation. In this work, we designed a ratiometric fluorescence DO sensing probe based on efficient energy transfer at long wavelength excitation. The oxygen probe Pt(ii )- meso -tetra(pentafluorophenyl)porphine (PtTFPP), the reference dye Coumarin 6 (C6) and Fe3 O4 NPs were encapsulated by amphiphilic silane at room temperature. The results indicate the important role of C6 molecules in the composite, serving as not only the ratiometric reference probe, but also the sensitizer of efficient energy transfer. The emission from PtTFPP can be greatly enhanced by 20 times based on the energy transfer pathway from C6 relative to that with the intrinsic excitation wavelength. DO sensing was successfully carried out based on ratiometric fluorescence in the imitation environment and at the cellular level under a confocal microscope. In addition, the cell magnetic separation function makes the composite possess great potential in DO sensing related medical applications.